Vanishing waters: water chemistry of temporary rock pools of the Western Ghats, India. Issue 1 (2nd November 2021) - Kulkarni, Aboli; Roy, Surajit; Yogeshwaran, Murugesan; Shigwan, Bhushan; Vijayan, Smrithy; Kshirsagar, Pranav; Datar, Mandar N.; Karthick, Balasubramanian
Abstract: The freshwater rockpools support high endemic biodiversity but are poorly studied habitats in the Western Ghats biodiversity hotspot. These freshwater rock pools are situated on outcrops at various elevations in the Western Ghats and are composed of different bedrocks such as laterite and basalt. We aimed to analyze the water quality, geographical position based differences in the water chemistry and the role of bedrock in determining the water chemistry of the rock pools. Our study showed a wide range of water quality variables such as pH, conductivity, and ionic contents that attributed to the natural variation. We observed a drastic variation in the anions and cations at low elevation pools. Rock type and precipitation are influencing the ionic concentration; for example, Calcium and Bromide could be attributed to the seasonal precipitation and geomorphology. This documentation of physicochemical properties of the Western Ghats rock pools can form a baseline for further detailed studies. HIGHLIGHTS: The water quality across rock outcrops of Western Ghats is documented. 80 different rockpools show high variation in the physicochemical composition. Water quality of the rock outcrops is suitable for supporting aquatic life. Rock type and precipitation influence the ionic concentration of water. Graphical Abstract